Design A Real-Time Fish Feeding Control System on The Internet of Things - Mia Febrianty; Asrizal Asrizal; Hufri Hufri; Rio Anshari (Department of Physics, Universitas Negeri Padang, 2023)
Scheduled feeding is very important in fish farming. Proper and scheduled feeding will increase yields and pond water quality. Fish farmers often ignore feeding according to fish needs. So that it worsens the water quality, as a result the yield and survival of fish decreases. This problem can be overcome by creating a system that can provide feed based on the ideal dose of feed to fish, in order to reduce pollution of pond waters and increase fish survival. This study aims to determine the specifications of accuracy and precision of laboratory scale systems and specifications of accuracy of field test scale systems. The research method used is engineering research method. The data obtained is measured by direct and indirect measurement techniques. This system uses wemos D1 mini, arduino cc, blynk software, RTC DS3231, load cell, DS18B20 and servo. The laboratory scale accuracy and precision specifications of the feeding control system on the measurement of the weight of the system tube feed are 99.70% and 99.80%, on the system container are 98.87% and 98.87%, while on the system temperature measurement are 98.10% and 97.96%. The accuracy value of the field test scale is 98.38%.Based on the results of testing the accuracy and precision of the fish feeding device, it is found that the design of a real time fish feeding system based on the internet of things can be used in monitoring and automatic feeding activities.